The english: english - Tubagus Rafli Akhdan Kusuma; Tegar Yudha Pratama; Muhsin Budiono; Andhika Satria Budiman; Buhori; Syahdhan Adiyah Islami Juventino (Universitas Muhammadiyah Bengkulu, 2026)
This study investigates the determinants of lubricant purchase intention in Surabaya and Sidoarjo by examining the influence of customer behavior, brand image, customer knowledge, and product price within a market increasingly challenged by the circulation of counterfeit lubricants. A quantitative approach was employed, involving 300 lubricant consumers and 100 lubricant repair shop owners from Surabaya and Sidoarjo. Logistic regression analysis was used to assess predictors of purchase intention among individual lubricant users, while log-linear modeling tested categorical relationships among repair shop owners regarding product selection and authenticity verification practices. The findings indicate that customer behavior, brand image, and customer knowledge significantly and positively influence purchase intention, with customer behavior emerging as the strongest predictor. Additionally, price perception contributes by enhancing perceptions of value and authenticity. These results underscore the importance of improving consumer education, strengthening brand credibility, and optimizing pricing strategies to mitigate the risk of counterfeiting. The study offers practical implications for lubricant manufacturers, distributors, and policymakers aiming to improve consumer decision-making and safeguard the lubricant market.